Cephalometric evaluation based on Steiner's analysis on adults of Bihar - Mrigank Shekhar Jha (Wolters Kluwer Medknow Publications, 2021)
Aim: To evaluate the mean cephalometric values for Steiner Analysis in bihar population. Objectives: To evaluate the cephalometric features of a bihar population and to present_an organized, comprehensive cephalometric norms for Steiner cephalometric analysis..To introduce mean values to assess skeletal, dental and soft tissue relationship using Steiner analysis for orthodontic diagnosis..To compare standards that will be derived with the earlier established norms for other population. Materials and Methods: The study was conducted in the Department of orthodontics and dentofacial orthopedics,Buddha Institute of Dental Sciences And Hospital,Patna(Bihar). The sample was collected from the out patient department of the same college. Source of the Data: The present analysis was made on lateral cephalograms of 60 subjects with well balanced and acceptable facial profile of Bihar population. The subjects were informed about the purpose of the study. Methods of Collection of Data: Subjects with age group of 18-26 years with dento-alveolar class I malocclusion and acceptable facial profile were selected by trained orthodontists, who belonged to the department of orthodontics and dentofacial orthopedics,Buddha Institute of Dental Sciences And Hospital. Results and Conclusion: There was increase in SNA angle, SNB angle, SND angle,in Bihar population than Caucasians. Bihar population has proclined and forwardly placed upper and lower incisors, which was indicative of bimaxillary protrusion as compared to Caucasians. Bihar population had protrusive upper and lower lips as compared to Caucasians. Bihar population males had tendency towards horizontal growth pattern of the mandible than females. Bihar females had more proclined lower incisors than males